2017
DOI: 10.3892/mmr.2017.8025
|View full text |Cite
|
Sign up to set email alerts
|

Reduced triglyceride accumulation due to overactivation of farnesoid X receptor signaling contributes to impaired liver regeneration following 50% hepatectomy in extra‑cholestatic liver tissue

Abstract: The aim of the present study was to investigate the role of triglyceride metabolism in the effect of obstructive cholestasis on liver regeneration following 50% partial hepatectomy (PH). Obstructive cholestatic rat models were achieved via ligation of the common bile duct (BDL). Following comparisons between hepatic pathological alterations with patients with perihilar cholangiocarcinoma, rats in the 7 day post‑BDL group were selected as the BDL model for subsequent experiments. Liver weight restoration, proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…These results further support that energy supplies in GF mice are altered considerably early during liver injury and it might be associated with an impaired capacity of the liver to regenerate as reported elsewhere. 56 The impact of the gut microbiota in the regulation of metabolic functions is still poorly understood. Bäckhed et al reported that in the absence of gut microbiota, mice have less hepatic fatty acids and adipose triglycerides compared to conventionally-raised mice.…”
Section: Discussionmentioning
confidence: 99%
“…These results further support that energy supplies in GF mice are altered considerably early during liver injury and it might be associated with an impaired capacity of the liver to regenerate as reported elsewhere. 56 The impact of the gut microbiota in the regulation of metabolic functions is still poorly understood. Bäckhed et al reported that in the absence of gut microbiota, mice have less hepatic fatty acids and adipose triglycerides compared to conventionally-raised mice.…”
Section: Discussionmentioning
confidence: 99%